Impact of Social Assistance Programs on Family Economic Welfare in Urban Environments: An Analysis of Equity and Community Engagement - Marson, Ferrant; Eagly, Pesando; Russell , Omvedt Morini (Institute for Law and Economics Studies, 2023)
This research investigates the impact of social assistance programs on the economic welfare of families within urban settings. It aims to discern the relationship between the utilization of social assistance programs and economic conditions, explore disparities in impact across socioeconomic strata, delve into the lived experiences of program beneficiaries, and provide recommendations for more equitable and effective policy implementation. A mixed-methods approach is employed, combining quantitative and qualitative methods. Quantitative data is collected through surveys and government records, while qualitative data is gathered via interviews and focus groups. The analysis encompasses statistical techniques and thematic coding. The research reveals a positive correlation between social assistance programs and economic improvements in urban households. It uncovers disparities in impact across income strata, with a more pronounced effect on lower-income families. Qualitative insights validate the experiences of program beneficiaries, emphasizing the programs' importance in providing essential resources and education support. The study's findings have substantial implications for policymakers, program administrators, and urban communities. Policymakers are urged to create more targeted, nuanced, and adaptive programs, administrators should streamline administrative processes and support adequacy, and communities are empowered to engage in program design. This research underscores the potential for a more responsive, equitable, and inclusive social assistance framework